Directional Hölder metric subregularity and application to tangent cones - Huynh Van Ngai; Nguyen Huu Tron; Phan Nhat Tinh (My University, 2017)
Directional Hölder metric subregularity and application to tangent cones
Keywords: Hölder subregularity; Tangent cones; Directional